"What Was That Word? It's Part of Ensuring Its Future Existence" Exploring Engagement Collectives at the European Commission's Joint Research Centre. (March 2023) - Völker, Thomas; Pereira, Ângela Guimarães
This paper provides an empirical analysis of an initiative to establish a Community of Practice on citizen engagement at the European Commission's (EC) Joint Research Centre (JRC). This initiative is one of the more recent attempts to institutionally stabilize citizen engagement in policy-making processes within the EC; such attempts are visible, for instance, in the political agenda of Ursula von der Leyen, whose sixth priority is a "new push for European democracy." Drawing on science and technology studies literature, this paper directs attention to models of participation and democracy visible in particular engagement activities and to the overarching rationales for engagement. We explore the sociomaterial engagement collectives that emerge in the practices and accounts of actors involved in establishing this CoP and show how these engagement collectives at the supra-national research service JRC are co-constitutive with the wider institutional settings and cultural–political configurations of the EC.